Associations of viscosity, stercobilin and bilirubin levels in meconium stained amniotic fluid to meconium aspiration syndrome - M. Sholeh Kosim; Lisyani B. Suromo; Chrisna Hendarwati (Paediatrica Indonesiana, 2011)
Background Meconium-stained amniotic fluid (MSAF) increases morbidity and mortality in neonates. Meconium aspiration syndrome (MAS) occurs in 2-9% of neonates with MSAF. Viscosity of MSAF is associated with the amount of the meconium release.Objective To determine the associations between viscosity and the presence of stercobilin and bilirubin in MSAF with MAS in neonates.Methods This observational cohort study was perfonned with term babies who were born v.ith MSAF in Kariadi Hospital from August 2009 to May 2010. Amniotic fluid specimens were taken at birth and neonates were observed for respiratory symptoms until the 5th day of life. Analysis was done by chi-square test, Fisher's exact test and relative risk.Results The majority of the 48 subjects were male, Mth mean gestational age of 39.9 (SD 1.73) weeks. Classification of MSAF as thick or thin was done by macroscopic examination Mth Kappa test 0.741. The MSAF tested ositively for stercobilin and bilirubin in 12/48 and 17/48 subjects, respectively. Thick MSAF correlated significantly to MAS (P=0.03) Mth a relative risk of 10.1 (95% CI 1.2 to 87 .6), while stercobilin and bilirubin presence did not.Conclusion Thick MSAF was associated Mth lvtAS and was a risk factor for MAS. Stercobilin and bilirubin presence in MSAF were not associated with MAS.